Dielectric Microsphere Coupled to a Plasmonic Nanowire: A Self‐Assembled Hybrid Optical Antenna. Issue 11 (29th March 2020) - Tiwari, Sunny; Taneja, Chetna; Sharma, Vandana; Vasista, Adarsh Bhaskar; Paul, Diptabrata; Pavan Kumar, G. V.
Abstract: Hybrid mesoscale structures that can combine dielectric optical resonances with plasmon‐polariton waves are of interest in chip‐scale nano‐optical communication and sensing. This experimental study shows how a fluorescent microsphere coupled to a silver nanowire can act as a remotely excited optical antenna. To realize this architecture, self‐assembly methodology is used to couple a fluorescent silica microsphere to a single silver nanowire. By exciting propagating surface plasmon polaritons at one end of the nanowire, remote excitation of the Stokes‐shifted whispering gallery modes (WGMs) of the microsphere is achieved. The WGM‐mediated fluorescence emission from the system is studied using Fourier plane optical microscopy, and the polar and azimuthal emission angles of the antenna are quantified. Interestingly, the thickness of the silver nanowires is shown to have direct ramification on the angular emission pattern, thus providing a design parameter to tune antenna characteristics. Furthermore, by employing 3D numerical simulations, electric near‐field of the gap junction between the microsphere and the nanowire is simulated and is transformed into far field. This work provides a self‐assembled optical antenna that combines dielectric optical resonances with propagating plasmons and can be harnessed in hybrid nonlinear nanophotonics and single‐molecule remote sensing. Abstract : Surface plasmon polaritons in a silver nanowire remotely excite the fluorescence of molecules coated on a dielectric microsphere at the silver nanowire–dielectric microsphere junction. The excited fluorescence is coupled to whispering gallery modes (WGMs) of the microsphere. These remotely excited WGMs outcouple directionally, which can be tuned by varying either the thickness of the silver nanowire or the diameter of the microsphere.